Role of the Supreme Court: policymaker or adjudicator? - Ervin, Sam J.; Clark, Ramsey (Washington : American Enterprise Institute for Public Policy Research, 1970)
This volume records the viewpoint of two distinguished authorities in the debate on Role of the Supreme Court: policymaker or adjudicator?
Includes bibliographical references.
lje 25/1/19
Loans
Keywords: Judiciary; Supreme court